Influence of gender and academic level on the development of digital competencies in university teachers: a multidisciplinary comparative analysis - Moreira-Choez, Jenniffer Sobeida; Lamus de Rodríguez, Tibisay Milene; Arias-Iturralde, María Cristina; Vega-Intriago, Jisson Oswaldo; Mendoza-Fernández, Verónica Monserrate; Zambrano-Acosta, Jimmy Manuel; Cardenas-Hinojosa, Ruben Dario (Frontiers in Education, 2024)
The digital era has transformed professional demands across all fields, particularly in higher education, where digital competencies are considered crucial for effective teaching performance. Based on this premise, the current study aimed to examine the digital competencies of faculty members at the State University of Milagro, focusing on the influences of gender and academic level. Employing a quantitative approach under the positivist paradigm, data from 279 faculty members were analyzed using the Higher Education Digital Competence Assessment Questionnaire, and a descriptive statistical analysis was conducted using SPSS. The results highlighted significant correlations among the dimensions of digital competencies, demonstrating that development in one specific competency could enhance skills in other areas. This interrelation emphasizes the integrative nature of digital technologies in the academic environment. The study revealed a high internal consistency in the evaluated competencies and underscored those differences according to gender and academic degree reflect variations in technological exposure and training. These findings point to the importance of adopting integrative educational strategies that promote equitable development of digital competencies among teaching staff.